2016
DOI: 10.1007/s00436-016-5174-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of double-stranded RNA virus in Trichomonas vaginalis Egyptian isolates and its association with pathogenicity

Abstract: Trichomoniasis is a common human sexually transmitted infection caused by Trichomonas vaginalis. The parasite can be infected with double-stranded RNA viruses (TVV). This viral infection may have important implications on trichomonal virulence and disease pathogenesis. This study aimed to determine the prevalence of T. vaginalis virus among isolates obtained from infected (symptomatic and asymptomatic) women in Ismailia City, Egypt, and to correlate the virus-infected isolates with the clinical manifestations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Only 1 study had a larger sample size than this study, with 500 TV isolates, of which 250 (50%) were TVV+ [16]. Unlike other STIs, TV infection rates are higher among women 25 years or older [27], compared to other age groups [3]. In this study, we found that TVV positivity was also associated with older age.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Only 1 study had a larger sample size than this study, with 500 TV isolates, of which 250 (50%) were TVV+ [16]. Unlike other STIs, TV infection rates are higher among women 25 years or older [27], compared to other age groups [3]. In this study, we found that TVV positivity was also associated with older age.…”
Section: Discussionmentioning
confidence: 46%
“…The authors suggested that TVV may have a role in the pathogenesis of trichomoniasis. El-Gayar et al [27] also found a significant association between TVV positivity and clinical manifestations of trichomoniasis among 40 TV-infected women in Egypt. However, the sample sizes of these studies were small and the associations between genital symptoms and TVV+ isolates have not been seen in larger studies, including our present study [28,30,31].…”
Section: Discussionmentioning
confidence: 90%
“…PCR was performed using specific primers described before ( 1 , 17 ) in a 25 μL mixture containing the template (3 μL of RT reaction), 2.5 U Taq DNA polymerase, 2.5 μL of 1 x PCR buffer, 20 pmol of each primer, 100 μmol dNTPs and 1.5 mmol MgCl 2 .Amplification was performed as follows: initial denaturing for 5 min at 95°C; 40 cycles of 94°C for 30 s, 51°C for 1 min and 72 °C for 40 s; extension at 72°C for 5 min and finally the PCR products were electrophoresed. Expected bands were found for TVV1 at 569 bp, TVV2 at 625 bp, TVV3 at 438 bp, and TVV4 at 514 bp.…”
Section: Methodsmentioning
confidence: 99%
“…A correlation between TVV symbiosis with T. vaginalis isolates and the severity of clinical symptoms of trichomoniasis in humans is emerging; while different papers report a positive association between TVV infection and the exacerbation of trichomoniasis symptoms, other authors have shown the absence of any correlation [53]. However, T. vaginalis and its virus appear to have a clear role in the subversion of the innate immune response and inflammation in the human host [54,55]. Although TVV is unable to infect and replicate in human cells [56], its presence can modulate the pro-inflammatory response in the human host, amplifying the innate response, and thus exacerbating clinical symptoms and the severity of disease.…”
Section: Trichomonas Vaginalis and Trichomonasvirusmentioning
confidence: 99%
“…Problems associated with human (or animal) immune response to the viral administration must of course be evaluated in advance. It is evident that TVV and LRV might be disadvantaged in this specific issue due to their adverse impact on the human immune system [54,55,95].…”
Section: Application Of Viruses By Their Direct Parasitopathic Activitymentioning
confidence: 99%